Development of an advanced nano-satellite (VELOX-IV) : automated instrumentation for testing - Hor, Zhi Xian (2016)
This report talks about the four different type of thrusters and why pulse plasma thruster is used. It will describe the characteristics of a pulse plasma thruster, the math governing the force related to the pulse plasma thruster and how a pulse plasma thruster works. Secondly, it will talk about the vacuum chamber available in the NTU Satellite Research Center as well as the thrust stand that will be used to do the calibration process. It gives a description of the components that made the thrust stand and the characteristic of this thrust stand. Thirdly, it shows the different instrument in the setup of a calibration system and how they are programmed to achieve what was required. The instruments include a function generator, a high voltage amplifier, an oscilloscope and a laser sensor. Fourthly, the process of the calibration will describe. The automation program will be explained and the choices it allows the user to choose will be described. It also highlights the problems encountered during the calibration. The calibration is split into two parts, one being the calibration of the thrust stand and the other being the characterizing of the thruster used. Lastly, it will be a discussion on the result collected as well as some future planning and problem solving suggestion.